-2+4(-8y+2)=-7(9y+1)-1

Simple and best practice solution for -2+4(-8y+2)=-7(9y+1)-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2+4(-8y+2)=-7(9y+1)-1 equation:


Simplifying
-2 + 4(-8y + 2) = -7(9y + 1) + -1

Reorder the terms:
-2 + 4(2 + -8y) = -7(9y + 1) + -1
-2 + (2 * 4 + -8y * 4) = -7(9y + 1) + -1
-2 + (8 + -32y) = -7(9y + 1) + -1

Combine like terms: -2 + 8 = 6
6 + -32y = -7(9y + 1) + -1

Reorder the terms:
6 + -32y = -7(1 + 9y) + -1
6 + -32y = (1 * -7 + 9y * -7) + -1
6 + -32y = (-7 + -63y) + -1

Reorder the terms:
6 + -32y = -7 + -1 + -63y

Combine like terms: -7 + -1 = -8
6 + -32y = -8 + -63y

Solving
6 + -32y = -8 + -63y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '63y' to each side of the equation.
6 + -32y + 63y = -8 + -63y + 63y

Combine like terms: -32y + 63y = 31y
6 + 31y = -8 + -63y + 63y

Combine like terms: -63y + 63y = 0
6 + 31y = -8 + 0
6 + 31y = -8

Add '-6' to each side of the equation.
6 + -6 + 31y = -8 + -6

Combine like terms: 6 + -6 = 0
0 + 31y = -8 + -6
31y = -8 + -6

Combine like terms: -8 + -6 = -14
31y = -14

Divide each side by '31'.
y = -0.4516129032

Simplifying
y = -0.4516129032

See similar equations:

| 60=68-7x | | -f^2-3t=0 | | 3y+x+4y+x-5=180 | | 1.2x-4.2=3.3 | | 3.4x-2=6.8 | | 5+x=33 | | 2(3x+1)+6=5(-2x-8) | | 2x-2-1=0 | | 2.32x=-46.73 | | 5x+9-8(x+1)=6X+5 | | 12x+6x= | | 1.8x+5.2=-3.5x-0.1 | | -3v-4=2v-19 | | x-(-24.82)=-71.94 | | 10-(2,5.4-3,8)= | | 12x+6x=18 | | 120x^2-8x-16=0 | | 6g+4(-8+5g)=1-g | | 81+x=33 | | 3m^3+24= | | f(-4)=16+3(-4)-7 | | x-29.65=-90.34 | | f(5)=2(25)+3(5)-4 | | c=kry | | 2x+6-3y=-12 | | r^3(c^3-125)+125(c^3-125)= | | 3.81x=69.24 | | 1.5p=1.23p+8 | | -41x=82 | | -24=4v | | (-71.24)+x=-81.49 | | 21+7x=-357 |

Equations solver categories